Increased Risk of Major Depressive Disorder After Cholecystectomy: A Nationwide Population-Based Cohort Study in Korea. Issue 4 (20th April 2021) - Jin, Eun Hyo; Han, Kyungdo; Lee, Dong Ho; Shin, Cheol Min; Lim, Joo Hyun; Yoon, Hyuk; Kim, Nayoung
Abstract : INTRODUCTION: This study investigated the risk of depression in Korean adults who underwent cholecystectomy and appeared for subsequent long-term follow-ups. A national population-based data set was used for analysis. METHODS: All patients (n = 111, 934) aged 40 years and older who underwent cholecystectomy between 2010 and 2015 and a control population (n = 223, 868), matched for age and sex, were identified from the database of the Korean National Health Insurance Corporation. The hazard ratio (HR) and 95% confidence interval (CI) of depression were estimated after cholecystectomy, and a Cox regression analysis was performed. RESULTS: The incidence of depression in the cholecystectomy group was 27.3 per 1, 000 person-years and that in the control group was 20.3 per 1, 000 person-years. Patients who underwent cholecystectomy showed an increased risk of major depressive disorder (MDD) with an adjusted HR (aHR) of 1.34 (95% CI: 1.31–1.37, P < 0.001). The mean follow-up period after a 1-year lag was 3.67 ± 1.79 years. In the subgroup analysis, the risk of developing MDD after cholecystectomy was relatively high in patients aged 40–49 years (aHR 1.51, 95% CI: 1.44–1.58) and in participants without diabetes mellitus (aHR: 1.36, 95% CI: 1.33–1.39), hypertension (aHR: 1.38, 95% CI: 1.34–1.42), or dyslipidemia (aHR: 1.35, 95% CI: 1.32–1.38). DISCUSSION: Compared with the control population, patients who underwent cholecystectomy exhibited an increased incidence of MDD. Thus, physicians should implement an enhanced program of MDD screening for at least several years after cholecystectomy.